Mesoporous ZnO thin films obtained from molecular layer deposited "zincones". Issue 37 (11th September 2019) - Perrotta, Alberto; Berger, Richard; Muralter, Fabian; Coclite, Anna Maria
Abstract : The synthesis of MLD-derived mesoporous ZnO with 20% of porosity is demonstrated and studied by advanced in situ characterization techniques. Abstract : The delivery of porous ZnO thin films represents a challenge due to the low porosity achievable by conventional thin film deposition methods. In this contribution, the synthesis of mesoporous ZnO thin films is demonstrated through calcination in air of hybrid Zn-based polymers (zincone) obtained by molecular layer deposition (MLD). The calcination process was followed as a function of temperature using X-ray reflectivity and diffraction, together with spectroscopic ellipsometry. Temperature ranges were identified for the removal of the organic ligands (120 °C) and ZnO crystallization (340 °C). The total porosity and open porosity were also determined by ellipsometric porosimetry (EP) and grazing incidence small-angle X-ray scattering (GISAXS). The calcination temperature was identified as a control parameter for obtaining different (open) porosity contents and pore size distributions (PSDs). Open porosity values of 12.6% and 19.6% were obtained by calcining the zincones up to 600 °C and 400 °C, respectively. Open PSDs with a mean value of 3.2 nm (400 °C) and 4.6 nm (600 °C) were obtained. The formation of larger slit-shaped pores was demonstrated at higher temperatures, due to the growth and coalescence of ZnO crystallites.